A comparison of online and offline consumer behaviour: An empirical study on a cinema shopping context. (September 2017) - Díaz, Asunción; Gómez, Mar; Molina, Arturo
Abstract: The main objective of this study is to analyse online vs. offline differences in consumer behaviour. To this end, through a proposal applied to cinemas in shopping centres, this study considers values and lifestyles as major factors that influence behaviours and intentions. The partial least squares (PLS) approach is used to evaluate the model. A multi-group analysis is conducted to compare consumers who buy tickets online with those who do so at a box office. We consider 391 valid cases. The results obtained show a link between the use of technology and its effects on behaviour. The relationships between values and behaviour as well as between behaviour and future intent are stronger among online consumers than the effects of lifestyles on behaviour. We consider relevant theoretical and empirical perspectives and offer critical recommendations of use to shopping centre managers, movie theatres, and intermediaries of this sector.